Advanced Serverless Architectures with Microsoft Azure : Design Complex Serverless Systems Quickly with the Scalability and Benefits of Azure. - Bass, Daniel (Packt Publishing Ltd, 2019)
Advanced Serverless Architectures with Microsoft Azure shows you what to do when the requirements are no longer simple and straightforward. You'll learn how to deliver the required features quickly by building systems that retain the scalability and benefits of serverless. You'll also learn the best practices that help you to avoid the ...